2008
DOI: 10.3748/wjg.14.5481
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic colonic metastases from primary squamous cell carcinoma of the lung with a positive fecal occult blood test

Abstract: We describe a 74-year-old man with a colonic metastatic squamous cell carcinoma (SCC) from the lung. His chest X-ray revealed an abnormal shadow in the right upper lobe. Computed tomography (CT) of the chest demonstrated a large lung tumor in the right upper lobe obstructing the right upper bronchus. Bronchoscopy revealed an easy-bleeding tumor in the right upper bronchus that was diagnosed as poorly differentiated squamous cell lung carcinoma. He underwent colonoscopy because he had a positive fecal occult bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 10 publications
0
46
1
1
Order By: Relevance
“…Although certain clinical studies and autopsy series (14)(15)(16) have shown adenocarcinoma to be prominent, as observed in the present study, other clinical studies (3,4) have demonstrated that squamous cell carcinoma, large cell carcinoma and pleomorphic carcinoma are more frequent (5,(17)(18)(19)(20)(21). Therefore, the histological type predominantly associated with gastrointestinal metastasis remains unclear.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Although certain clinical studies and autopsy series (14)(15)(16) have shown adenocarcinoma to be prominent, as observed in the present study, other clinical studies (3,4) have demonstrated that squamous cell carcinoma, large cell carcinoma and pleomorphic carcinoma are more frequent (5,(17)(18)(19)(20)(21). Therefore, the histological type predominantly associated with gastrointestinal metastasis remains unclear.…”
Section: Discussioncontrasting
confidence: 41%
“…To the best of our knowledge, only a few studies of long-term survival in cases of large bowel metastasis of lung cancer have been published (17,31). In the current study, we hypothesize that the long-term survival in 1 case was due to the presence of solitary metastasis with resectable lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic SCC to the colon has been described in the literature but, typically, these tumors originate from a pulmonary tumor. 4,5 Although metastasis to the rectum from ovarian squamous cell carcinoma has been described, 6,7 to our knowledge, this is the first case of recurrent SCC to the colon arising from the malignant degeneration of a mature cystic teratoma.…”
Section: Discussionmentioning
confidence: 87%
“…Most CRCs are in the form of adenocarcinomas arising from the colonic mucosa; however, metastatic malignancy in color as a colon is extremely rare. A review of the literature disclosed that only a few cases have reported the occurrence of this rare condition from renal cell carcinoma, bronchogenic cancer [2], and breast cancer [3]. Secondary colonic neogrowth originating from asymptomatic gastric stump is extremely rare.…”
Section: Introductionmentioning
confidence: 99%